Knowledge and practice in the management of asymptomatic hyperuricemia among primary health care physicians in Jeddah, Western Region of Saudi Arabia - Alqarni, Norah A. (Saudi Med J, 2018)
OBJECTIVES: To assess knowledge and practice levels in asymptomatic hyperuricemia (AH) and investigate predictors of urate-lowering therapy (ULT) misprescribing among primary health care (PHC) physicians. METHODS: A cross-sectional study was conducted among 201 PHC physicians from December 2017 to May 2018. A based clinical guidelines for hyperuricemia management from American Professional Organizations, a semi-structured questionnaire was administered to collect demographic and professional data; knowledge and practice levels in management of AH; and barriers to the management of hyperuricemia and gout, with focus of the misprescribing of ULT in AH. A 2-stage stratified sampling technique was used to select 4 PHC centers were from each of the 5 advisory sectors in Jeddah, Kingdom of Saudi Arabia; and to recruit a minimum of 10 eligible participants per primary health care center (PHCC). Binary logistic regression was used to analyze predictors of ULT misuse in AH. RESULTS: Only 32.8% participating physicians had adequate knowledge about AH. Regarding practice, while majority (88.1%) correctly recommended a low-purine diet and lifestyle changes to patients, almost half misprescribed ULT and 10.9% misprescribed non-steroid anti-inflammatory drugs. Lack of knowledge and awareness about guidelines were the most frequently self-reported barriers to adequate practice. Predictors of ULT misuse included the percentage of patients having gout (1-10%: OR=5.40, p=0.047) or receiving ULT (>10-20%: OR=20.02, p=0.001)among patients seen in clinic, attendance of rheumatology conferences (OR=2.55, p=0.017), and having a close relative with hyperuricemia or gout (OR=2.45, p=0.026). CONCLUSION: There are inadequate levels of knowledge regarding AH among Saudi PHC physicians increasing risk of malpractice including misprescription of ULT and anti-inflammatory medications.